The problem of life imprisonment as a punitive response to the crime of rape of minors - Bustillos Cuba, Rolando (2023)
The author analyzes the problem of the application of life imprisonment in the crime of rape of minors, provided for in Article 173 of the Peruvian Criminal Code. He considers that although the Peruvian Supreme Court and Constitutional Court have reaffirmed its constitutionality, in the face of exceptional situations that arise in each particular case (grounds for reduction of punishability, procedural bonuses and personal circumstances of both the victim and the aggressor), the criminal law has not provided for the possibility of reducing the penalty to limits below the legal minimum, which in many cases has led to the legal operator of lower instances, despite such assumptions, to impose disproportionate penalties, far from the principle of guilt. This had to be corrected by the Supreme Court, and a context of legal insecurity was manifested that denaturalizes the purposes of criminal law as a means of social control, which cannot admit irrationality or arbitrariness in defining penalties. In view of this, it is proposed to modify said criminal law to allow the selective reduction of the penalty to limits lower than the legal minimum in exceptional situations, so that the judge has a margin of flexibility and imposes a temporary penalty in its just measure.